2019
DOI: 10.4103/njms.njms_15_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and correlation between functional and histological staging of oral submucous fibrosis: A clinicohistopathologic study

Abstract: Background and Objective: Oral submucous fibrosis (OSMF) is a precancerous condition. It is widespread in the Asian subcontinent, with India bearing most of the burden. It is characterized by mucosal rigidity of varying intensity due to the fibroelastic changes of the juxta epithelial layer, resulting in a progressive inability to open the mouth. Early recognition with accurate staging of the disease and appropriate treatment planning is of utmost importance to prevent the malignant transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Similar cases are reported from India and adjacent countries in children who had a history of areca nut chewing or tobacco consumption [ 15 , 16 ]. Males clearly outnumbered the females, which is in concordance with the previously reported studies, irrespective of the region and country [ 13 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar cases are reported from India and adjacent countries in children who had a history of areca nut chewing or tobacco consumption [ 15 , 16 ]. Males clearly outnumbered the females, which is in concordance with the previously reported studies, irrespective of the region and country [ 13 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The data pertaining to the correlation between functional or clinical and histopathological stagings is conflicting [ 17 , 23 , 24 ]. While most studies showed no correlation between the histological and clinical staging systems, we found a significant correlation between the histological and clinical staging of OSMF implying that clinically advanced OSMF shows extensive fibrosis and constricted vasculature histopathologically.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was carried out by Bhatt et al . [ 30 ] in 2018. They found definitive correlation between functional and histological stages of OSMF.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO definition of OLK, white lesions with the respective clinical manifestations and pathological features are excluded, such as leukoedema, linea alba, chronic biting irritation, white spongy nevus, and other potentially malignant disorders such as discoid lupus erythematosus and lichen planus. The pathology of OSF is characterized by hypercollagenous deposits in the subepithelial connective tissue of the oral mucosa and local inflammation of the lamina propria or deep connective tissue, as well as muscle degenerative changes 26 . In addition, epithelial cell atrophy, and loss of rete pegs have been reported 27 .…”
Section: Methodsmentioning
confidence: 99%